2020
DOI: 10.1111/anu.13157
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential synergistic effects between dietary adenosine and inosine monophosphate on growth performance and acute stress‐induced immune responses of hybrid striped bassMorone chrysops × Morone saxatilis

Abstract: Two experiments were carried out to evaluate the effects of dietary adenosine monophosphate (AMP) and inosine monophosphate (IMP) on growth performance and acute stress‐induced immune response of hybrid striped bass (HSB). Nine isonitrogenous and isolipidic diets were prepared including a basal diet and eight treatments consisting of singular or combined additions of 0.5% AMP and 0.5% IMP, and combinations of 0.25% AMP and 0.25% IMP from each of two suppliers, Sigma‐Aldrich and Chem‐Impex. The first experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Overall, these results indicated that combination of two or more alternative protein could substitute more FM in LBM feed, and meet the fish nutritional requirement. In addition, functional additives, such as paraprobiotics, nucleotide and phytogenic extracts, have been widely used in fish aquatic feeds (de Cruz et al., 2020; Siciliano et al., 2021). In LMB diet, Xie et al .…”
Section: Combination Of Alternative Proteins or Protein With Function...mentioning
confidence: 99%
“…Overall, these results indicated that combination of two or more alternative protein could substitute more FM in LBM feed, and meet the fish nutritional requirement. In addition, functional additives, such as paraprobiotics, nucleotide and phytogenic extracts, have been widely used in fish aquatic feeds (de Cruz et al., 2020; Siciliano et al., 2021). In LMB diet, Xie et al .…”
Section: Combination Of Alternative Proteins or Protein With Function...mentioning
confidence: 99%
“…Six isonitrogenous (45.16% protein) and isolipidic (17.43% lipids) diets were formulated to contain 2 low different FM levels (20 and 10%) as control treatments. Then, nucleotides (NT) and nucleic acid (NA) were added at the same dosage of 500 mg kg feed -1 in accordance with recent recommendations on same and other fish species (De Cruz et al, 2020;El-Nokrashy et al, 2021;Magouz et al, 2021). Experimental diets were produced via extrusion (pellet size = 2.0 mm) by the Danish Technological Institute (Taastrup, Denmark).…”
Section: Experimental Diets and Additive Dosagesmentioning
confidence: 99%